Distribusi Temporal Jenis Arthropoda Yang Ada pada Tumbuhan Krokot (Portulaca Oleracea L. ) di Lahan Pertanian Cabai Merah - Syukur Harahap; Yusmaidar Sepriani; Hilwa Walida; Khairul Rizal (AGROMAKNA: Jurnal Pertanian dan Peternakan, 2026)
Pests are animals that damage crops and generally harm farmers from an economic perspective, so humans will always pay attention to them, in order to increase agricultural yields, otherwise the yields will decrease. The purpose of this study was to analyze and describe the temporal distribution of arthropods on purslane (Portulaca oleracea L.) on red chili farms, Afdeling II Village, West Bilah Subdistrict, Labuhanbatu Regency. This research method is descriptive exploratory research with a quantitative approach. This is to describe and analyze the temporal distribution of arthropods in purslane (Portulaca oleracea L.). Data was observed from the arrival of arthropods at a predetermined time, namely three 3 observation times, including: time I (07.00-08.00), time II (12.00-13.00), and time III (16.00-17.00) for 10 minutes. Each time the observation was repeated 4 times. The results of this study showed that the daily visits of arthropods at 12.00-13.00 were higher than the daily visits at 07.00-08.00 and 16.00-17.00. Each family of arthropods has a different level of daily visits at each time of arrival which is caused by internal factors (physiological, reproductive ability, life cycle, age) and external factors (physical factors, food, temperature and humidity). The daily visit frequency of this arthropod indicates that purslane (Portulaca oleracea L.) is a habitat for arthropods and can be used as a refugia plant